Revisiting exchange concept: a rationale for marketing mix in Islamic marketing / Johari Abdullah - Abdullah, Johari (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
Marketing mix has been the cornerstone of the discipline and dominating marketing early thought. This concept has been the focal point in the development of conventional managerial paradigm with strong adherence to its normative pillars of ‘4 Ps’. History has shown that a new paradigm constantly shifting the status quo of such concept into more advance findings. The objective of this paper is to present the rationale of marketing mix in Islamic marketing. Despite the evolution of marketing mix paradigm over more than 40 years, it is undeniable that such classical marketing canon has its root from concept of exchange. By using both qualitative and quantitative approaches in the development of instruments has led to the development of the 5Cs model. It is aimed to proposed a more advance finding derived from an Islamic perspective towards the concept. In depth literature review and survey has found a distinct set of marketing mix variables catering to Muslim consumer that are in line with Islamic principles. 5Cs models of Commitment, Characteristics, Conformity, Conscience, Customer centric offers a new way of marketing to Muslim consumers governed by Islamic principles and injunctions. Therefore, 5Cs model can be applied in many areas, for instance in Halal industry. It is recommended that business and academia will apply and further develop the model as it will enrich the framework and as to remain relevant.